Sensitive and simultaneous surface plasmon resonance detection of free and p53-bound MDM2 proteins from human sarcomas. Issue 9 (11th April 2018) - Wu, Ling; Tang, Hailin; Hu, Shengqiang; Xia, Yonghong; Lu, Zhixuan; Fan, Yujuan; Wang, Zixiao; Yi, Xinyao; Zhou, Feimeng; Wang, Jianxiu
Abstract : Sensitive SPR determination of free and p53-bound MDM2 proteins from sarcoma tissue extracts was carried out in fluidic channels covered with the consensus ds-DNA/p53 conjugate and the consensus ds-DNA, respectively. Abstract : Murine double minute 2 (MDM2) is an oncoprotein mediating the degradation of the tumor suppressor p53 protein. The physiological levels of MDM2 protein are closely related to malignant transformation and tumor growth. In this work, the simultaneous and label-free determination of free and p53-bound MDM2 proteins from sarcoma tissue extracts was conducted using a dual-channel surface plasmon resonance (SPR) instrument. Free MDM2 protein was measured in one fluidic channel covered with the consensus double-stranded (ds)-DNA/p53 conjugate, while MDM2 bound to p53 was captured by the consensus ds-DNA immobilized onto the other channel. To achieve higher sensitivity and to confirm specificity, an MDM2-specific monoclonal antibody (2A10) was used to recognize both the free and p53-bound MDM2 proteins. The resultant method afforded a detection limit of 0.55 pM of MDM2. The amenability of the method to the analysis of free and p53-bound MDM2 proteins was demonstrated for normal and sarcoma tissue extracts from three patients. Our data reveal that both free and total MDM2 (free and bound forms combined) proteins from sarcoma tissue extracts are of much higher concentrations than those from normal tissue extracts and the p53-bound MDM2 protein only constitutes a small fraction of the total MDM2 concentration. In comparison with enzyme-linked immunosorbent assay (ELISA), the proposed method possesses higher sensitivity, is more cost-effective, and is capable of determining free and p53-bound MDM2 proteins in clinical samples.